E-Service Quality and Loyalty Driving E-Satisfaction and E-WOM in Higher Education - Vi T. T. Nguyen; Tue G. Truong; Thanh D. Nguyen (Emerging Science Journal, 2025)
This study examines the influence of core e-service quality dimensions, information quality, website performance, and website confidentiality, on perceived emotional value, e-satisfaction, student loyalty, and electronic word-of-mouth (e-WOM) within the digital delivery of higher education services in Vietnam. Drawing upon the Stimulus–Organism–Response (SOR) framework, the Expectation–Confirmation Theory (ECT), and the Value-Based Adoption Model (VAM), this research investigates behavioral outcomes through psychological mediators. Data were collected from 311 university students with prior experience in using their universities’ electronic service platforms, including learning and academic management systems. Measurement scales were adapted from established studies, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS–SEM). The results reveal that e-service quality positively influences perceived emotional value, which subsequently drives e-satisfaction, student loyalty, and e-WOM. Furthermore, student loyalty reinforces e-WOM, underscoring the critical role of digital engagement in higher education. This study contributes to existing theory by integrating service quality dimensions, emotional responses, and behavioral intentions into a unified model. It also offers practical insights for enhancing student engagement, optimizing digital learning environments, and strengthening institutional reputation in today’s increasingly competitive digital education landscape.